2007
DOI: 10.36691/rja98
|View full text |Cite
|
Sign up to set email alerts
|

Activated zinc pyrithione. Mechanism of action. Clinical application

Abstract: Activated zinc pyrithione (ZP) has a number of contributory pharmacodynamic effects that provide it's efficacy in psoriasis and atopic dermatitis. Because of ZP impairs the integrity of cell membranes it is active against many bacterial and yeast species. In psoriasis and atopic dermatitis ZP therapy is accompanied by accelerated cells' apoptosis of lower layers of epidermis and atopic inflammatory infiltrate as well as by decrease in skin neutrophils and lymphocytes. The broad spectrum of pharmacological acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…Activated zinc pyrithione can bind to phospholipids and chelate metal cations, activate apoptosis, and inhibit regeneration. The antimicrobial and antifungal actions are based on the ability of this drug to disrupt the integrity of cell membranes [29] . In a comparative study of the anti-inflammatory activity of zinc pyrithione in a laboratory model of psoriasis, it was found that the anti-inflammatory effect of activated zinc pyrithione was insignificantly inferior to betamethasone and superior to zinc pyrithione [30,31] .…”
Section: Introductionmentioning
confidence: 99%
“…Activated zinc pyrithione can bind to phospholipids and chelate metal cations, activate apoptosis, and inhibit regeneration. The antimicrobial and antifungal actions are based on the ability of this drug to disrupt the integrity of cell membranes [29] . In a comparative study of the anti-inflammatory activity of zinc pyrithione in a laboratory model of psoriasis, it was found that the anti-inflammatory effect of activated zinc pyrithione was insignificantly inferior to betamethasone and superior to zinc pyrithione [30,31] .…”
Section: Introductionmentioning
confidence: 99%